PENDIDIKAN REPRODUKSI DALAM PEMBELAJARAN FIQIH MI (Studi di MIN 22 Hulu Sungai Utara dan MI Normal Islam Rakha Amuntai) - Hikmatu Ruwaida (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Reproductive health problems are now warmly spoken by the public, especially among parents. Parents are increasingly anxious as many free-sex cases and pornography and pornographic publications have been readily accessible to anyone including by minors. In elementary school, especially the MI material will be very good when given through the Fiqh subjects, where Islam gives more attention to the cleanliness of one to-until clean is the key to the implementation of worship. Children must be equipped with good religious education including the problem of reproductive organs cleanliness in the perspective of the law Syara, which is also supported by the provision of understanding and awareness of students in the importance of maintaining the safety of organs It is not used prematurely and remains healthy and spared from various diseases. In this AM research will be revealed how the teacher teaches reproductive education to the son of MI. This research uses qualitative research, with a case study approach. Data collection techniques using interviews, observations and documentation. Data analysis includes analysis of single and cross-site data sites with data analysis techniques consisting of data reduction, data presentation, and withdrawal of conclusions. The research aims to show that in general, MI teachers in both schools provide the teaching of this reproductive function indirectly. Indirectly, in this lesson in Fiqh, there is already a separate material about menstruation and circumcision, at the time of teaching the message of moral messages, especially the rules of sharia that organize them. Keywords: reproductive education, fiqh-MI Learning